2019
DOI: 10.3747/co.26.4951
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Reasons for Overuse of Contralateral Prophylactic Mastectomy in Canada

Abstract: Background Contralateral prophylactic mastectomy (cpm) in women with known unilateral breast cancer (bca) has been increasing despite the lack of supportive evidence. The purpose of the present study was to identify the determinants of cpm in women with unilateral bca.Methods This qualitative descriptive study used semi-structured interviews informed by the Theoretical Domains Framework. We interviewed 74 key informants (surgical oncologists, plastic surgeons, medical oncologists, radiation oncologists, nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Women may experience a heightened psychological reaction, fearing an event that is theoretical, of low likelihood, and occurring well into the future. Squires et al reported that anxiety from fear had influenced women with breast cancer to preferring contralateral mastectomy. Graves et al associated breast cancer–specific distress with contralateral prophylactic mastectomy.…”
Section: Distress and Fear Of Recurrencementioning
confidence: 99%
See 3 more Smart Citations
“…Women may experience a heightened psychological reaction, fearing an event that is theoretical, of low likelihood, and occurring well into the future. Squires et al reported that anxiety from fear had influenced women with breast cancer to preferring contralateral mastectomy. Graves et al associated breast cancer–specific distress with contralateral prophylactic mastectomy.…”
Section: Distress and Fear Of Recurrencementioning
confidence: 99%
“…In Canada, clinicians seem to not raise the issue of contralateral prophylactic mastectomy unless the patient brings it up or is considering unilateral mastectomy . Canadian physicians have reported that, if a woman had expressed a desire for contralateral prophylactic mastectomy, it was difficult to change her mind.…”
Section: Physician Preferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…20 As contemporary reconstructive practices provide more realistic breast reconstructions, the desire for more symmetrical, esthetic breasts play a key role in the decision-making process. 45 This is subsequently acknowledged by CPM consensus statements; however, greater emphasis must be placed on the multi-specialty approach to this decision and the utilization of psychological input to mitigate the anxiety concerns. 16,26,46 Patients should have pre-operative counseling which addresses the irreversible nature and potential cosmetic and emotional consequences of CPM as patients have been documented…”
Section: Ta B L E 1 Coverage Criteria For Contralateral Prophylactic Mastectomymentioning
confidence: 99%